IMPACT OF INTEREST AND EXCHANGE RATES ON STOCK MARKET PERFORMANCE IN SUB-SAHARAN AFRICA - CHIGOSIMUZO, AGUNOBI CHRISTOPHER; JUSTIN, DAVID; OLUWATUYI, FOLORUNSO (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study investigated the impact of macroeconomic variables specifically, central bank policy rates (interest rates) and nominal exchange rates on stock market performance in Sub-Saharan Africa, focusing on Nigeria, South Africa, Ghana, and Namibia. Motivated by the need to understand how economic fundamentals influence financial markets in developing economies, the study employed quarterly panel data from 2010Q2 to 2025Q1. The analysis utilized a Fixed Effects Model to account for country-specific heterogeneity in assessing stock market performance, proxied by the All Share Index (ASI). The findings revealed that nominal exchange rates had a positive but statistically insignificant impact on stock market performance, suggesting a potentially weak but directional relationship. In contrast, interest rates showed a negative and statistically insignificant effect, indicating limited immediate influence on market behaviour. Other macroeconomic control variables including inflation and foreign direct investment also exhibited no significant impact. The results highlight the complex nature of macro-financial interactions in the region and underscore the need for cautious monetary policy calibration. The study concluded that while macroeconomic fundamentals do influence market trajectories, their effects may be moderated by structural and institutional factors unique to Sub-Saharan Africa. It recommends strengthening financial market infrastructure and deepening macroeconomic coordination to enhance resilience and investor confidence.